Contemporary Approaches for Evidence-Based Pharmacotherapy. (April 2013) - Gim, Suzanna; Vincent, William R.
Evidence-based medicine (EBM) is the conscientious, explicit, and judicious use of current best evidence in making decisions about the care of individual patients. This article provides simple ways to practice everyday EBM by (1) asking patient-specific clinical questions, (2) finding the most relevant, best evidence, (3) critically appraising evidence to ensure validity, (4) applying evidence to practice, and (5) using available tools to stay abreast of relevant and valid evidence as it becomes available.